2010
DOI: 10.1158/1535-7163.mct-09-1212
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Src Kinase Signaling Attenuates Pancreatic Tumorigenesis

Abstract: Elevated Src expression correlates with malignant potential and metastatic disease in many tumors including pancreas cancer. We sought to characterize the molecular effects of Src kinase inhibition with dasatinib (BMS-354825) a novel, multi-targeted kinase inhibitor that targets Src family kinases, in pancreas ductal adenocarcinoma (PDA). We identified sensitive and resistant PDA cell lines to dasatinib treatment and tested the molecular effects of Src inhibition in vitro and in vivo. We show for the first tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
97
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 41 publications
13
97
0
Order By: Relevance
“…It has been well established that STAT3 activation regulates oncogenic signaling in many tumor types and leads to increased cell survival, proliferation, and tumor growth (43)(44)(45)(46). Furthermore, recent studies have also shown that activated STAT3 is a biomarker of resistance to Src inhibition with dasatinib treatment in resistant PANC-1 cells (32,36). Consistent with these reports, we found that dasatinib did not inhibit the STAT3 phosphorylation in PANC-1 cells in vitro.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been well established that STAT3 activation regulates oncogenic signaling in many tumor types and leads to increased cell survival, proliferation, and tumor growth (43)(44)(45)(46). Furthermore, recent studies have also shown that activated STAT3 is a biomarker of resistance to Src inhibition with dasatinib treatment in resistant PANC-1 cells (32,36). Consistent with these reports, we found that dasatinib did not inhibit the STAT3 phosphorylation in PANC-1 cells in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…Significantly, gemcitabine appeared to increase the phosphorylation of EGFR and ERK in both BxPC-3 and PANC-1 cells at a concentration of 10 mmol/L, which is consistent with a previous report (35). Of note, SKLB261 reduced the STAT3 phosphorylation in a concentration-dependent manner in both BxPC-3 cells and PANC-1 cells, which is reported to be one of the mechanisms of resistance to Src inhibition in pancreatic cancer cells (36).…”
Section: Blockade Of the Activation Of Multiple Downstream Signaling supporting
confidence: 91%
“…Dasatinib decreases cell proliferation, cell cycle progression, anchorage independent growth, migration, and invasion in PDAC cell lines in vitro [10,19] and significantly inhibited the development of metastases in vivo with no effect on overall survival, probably due to progression of the primary tumor. Thus, there is evidence to support the hypothesis that Src kinase inhibitors may function as anti-metastatic agents in PDAC [10].…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of pancreatic cancer cell lines in vitro with dasatinib inhibits invasion and migration at concentrations that inhibit Src kinase activity [10,19], as well as proliferation and anchorage-independent cell growth [19,20]. Dasatinib inhibits pancreatic tumor growth in vivo in xenograft models [19,20] and inhibits the development of metastases in vivo in a genetically-engineered mouse model of pancreatic cancer [10], suggesting that this agent might best be used in patients without metastatic disease to prevent development of distant metastases. Unpublished data from the first author's laboratory suggests that there was a trend to improved overall survival with the combination of gemcitabine and dasatinib compared to dasatinib alone in a genetically-engineered mouse model of pancreatic cancer that did not reach statistical significance (p = 0.08).…”
Section: Introductionmentioning
confidence: 99%
“…There are significant preclinical data to support the rationale for Src inhibition as a potentially effective therapeutic target in PCa [3][4][5][6]. However, the presumption that a single biologic agent would significantly improve survival in metastatic PCa is inconsistent with prior clinical investigation and preclinical data.…”
mentioning
confidence: 99%